PENGARUH PENERAPAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BPR NBP 32 KARAWANG - Muhammad Akmal Rizki Faiz; Syifa Pramudita Faddila (Jurnal Pijar, 2023)
Employee performance is still a major factor in a company so there are several strategies to improve employee performance, namely work discipline. This study aims to determine whether the independent variables have a partial or simultaneous influence on the dependent variable. The method in this study is explanatory research with a quantitative approach using validity, reliability, classic assumption tests, multiple linear regression analysis, multiple correlation, coefficient of determination, t test and F test using SPSS (statistical package for social) data processing version 20.0. The results of this study can be concluded that work discipline has a partial influence. Thus, this research is expected to contribute or be used as material for consideration in running the industry to improve employee performance